2007
DOI: 10.1074/jbc.m705898200
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-associated Box Repressor Domain Can Trigger de Novo Promoter Methylation during Mouse Early Embryogenesis

Abstract: The Krüppel-associated box (KRAB) domain is a transcriptional repression module responsible for the DNA binding-dependent gene silencing activity of hundreds of vertebrate zinc finger proteins. We previously exploited KRAB-mediated repression within the context of a tet repressor-KRAB fusion protein and of lentiviral vectors to create a method of external gene control. We demonstrated that with this system transcriptional silencing was fully reversible in cell culture as well as in vivo. Here we reveal that, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 37 publications
7
107
2
Order By: Relevance
“…Dox Treatment and Analysis-Mouse embryonic fibroblasts were isolated as described (24) and where applicable were grown in the presence of 1 g/ml dox (Sigma). Dox was administered to mice in their drinking water, which was also supplemented with 4% glucose at a concentration of either 2 g/liter or 0.2 g/liter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dox Treatment and Analysis-Mouse embryonic fibroblasts were isolated as described (24) and where applicable were grown in the presence of 1 g/ml dox (Sigma). Dox was administered to mice in their drinking water, which was also supplemented with 4% glucose at a concentration of either 2 g/liter or 0.2 g/liter.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent work revealed that, in these circumstances, the tethering of KRAB to the vicinity of a promoter led to its de novo DNA methylation, and hence to its stable silencing even in the absence of repressor binding (24). Importantly, in these cases KRAB was targeted to the vicinity of a CpG-island containing promoter in the context of a lentiviral vector.…”
mentioning
confidence: 99%
“…Will the disease still develop if a correction of SMN2 splicing is discontinued after the first phases of post-natal life? Mouse models for SMA 28,29 and transgenic mice expressing the tTR-KRAB regulator 30 are available. If these genotypes are combined with the regulatable U7-ESE-B cassette, many of the above questions could be addressed, simply by providing doxycycline through drinking water at different times during ontogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether and how precisely this will be feasible will depend on the repression and induction kinetics observed in vivo (in our cell culture system B48 h and B120 h were necessary for full induction and repression, respectively) and on whether the silencing will not be irreversible in vivo. 30 Efficient transfer of the therapeutic U7-ESE-B cassette to motoneurons will need to be developed to approach a true somatic gene therapy for SMA. This may well (a and b) HS2 cells transduced with the regulatable U7 and KRAB lentiviral vectors, equilibrated in the repressed state, were induced with 1 mg ml À1 doxycycline.…”
Section: Discussionmentioning
confidence: 99%
“…Initially termed binding factor A, this 1.3-MDa multisubunit complex contains TRIM28 as a repressor subunit (Reik 2007) and the KRAB-ZFP809 that serves as its sequence-specific DNA-binding partner (Wolf and Goff 2009). TRIM28 links the DNA methylation and KRAB-ZFP repressive machineries as shown by tethering a doxycycline-controllable KRAB domain to a lentiviral construct in vivo (Wiznerowicz et al 2007). Here, a green fluorescent protein (GFP) reporter gene was found to be expressed only if recruitment of the repressive KRAB-ZFP was prevented by adding doxycycline in a narrow time window right after fertilization (between E0.5 and E3.5).…”
Section: The Trim28 Complex In Retrotransposon Regulationmentioning
confidence: 99%